A Meta-Analysis of Researches on Implementing the Semester System: The Way Ahead? - Sharma, Netra Prasad (Tribhuvan University Journal, 2016)
At present, Tribhuvan University (TU) seems to be in a sort of dilemma as to whether or not the semester system can be implemented in the programmers run by its faculties. Although TU authorities are still in extended discourse with the concerned stakeholders for the expansion of the semester programme, I sense some dilemma in the steps to be taken, the confusion propped by the fact that even the Master’s programmes under the semester system have not been extended horizontally to the campuses other than the Central Departments at Kirtipur and the two other campuses in the valley only in science education. In this context, this article attempts to synthesize the research findings akin to the semester system and, based on the researches reviewed, points out the possible hurdles that need to be taken into consideration in advance and handled with great caution. The article argues that, despite some socioeconomic challenges, the semester system is better than the annual one and that it is the responsibility of all stakeholders to contribute to the implementation and success of the semester programmes.